Digital Triggers of Adolescent Anxiety in Oyo Town, Nigeria - Victor Ayodeji Fehintola; Tobi Moses Ogunniyi (MASI Mandiri Edukasi, 2025)
Anxiety disorders represent one of the most prevalent mental health challenges among adolescents globally, with significant implications for academic performance, social development, and overall well-being. While extensive research has examined the impact of digital technology on mental health in Western contexts, there remains a critical gap in understanding these relationships in smaller urban centres in Africa. This study addressed this gap by investigating the relationships between social media use intensity, cyberbullying victimisation, online peer support, and anxiety levels among adolescents in Oyo Town, Nigeria. A cross-sectional correlational design was employed with 250 adolescents (mean age=15.2years, SD=1.8;52% female) selected through multistage sampling from four secondary schools across two Local Government Areas. Data were collected using validated instruments: the SMUIS, CVS, OSS, and the SCARED scales. Pearson correlation analysis revealed significant positive correlations between anxiety levels and both social media use intensity (r=0.483,p<.005) and cyberbullying victimisation (r=0.652,p<.005), while online peer support demonstrated a significant protective effect (r=-0.316, p<.001). Multiple regression analysis identified cyberbullying exposure as the strongest predictor of anxiety levels (β=.526,p<.001), followed by social media use intensity (β=.312,p<.001), with online peer support serving as a significant protective factor (β=-.241,p<.001). These digital variables accounted for 64.3% of the variance in adolescent anxiety levels, indicating a substantial influence of digital experiences on youth mental health in this context. The findings underscore the critical need for comprehensive cyberbullying prevention programs and culturally appropriate digital literacy interventions in Nigerian educational settings, while highlighting the potential of online peer support networks as protective mechanisms against adolescent anxiety.